Peran Industri Perhotelan dalam Mendukung Pariwisata Heritage di Candi Tebing Tegalinggah Gianyar, Bali - Eko Moh. Romi Kurniawan; Rizka Elvira Parindur; Ngakan Putu Purwita; Jeanny Pricilia Anneke W (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to explore the role of the hospitality industry in supporting the development of heritage tourism at Candi Tebing Tegalinggah, Gianyar, Bali. The research employs a qualitative approach with data collection techniques including in-depth interviews and Focus Group Discussions (FGD) with hotel managers, hotel staff, heritage site managers, and tourists. Additionally, secondary data was obtained from documents, literature, and relevant reports. Data analysis was performed descriptively, focusing on identifying key themes from the discussions and interviews. The results indicate that the role of the hospitality industry in supporting heritage tourism at Candi Tebing Tegalinggah is still suboptimal. Despite the awareness of the heritage site's potential, hotels around the site have not fully leveraged this opportunity through integrated cultural tourism programs. Information about the site provided by hotels is also limited, reducing tourists' interest in visiting. Some hotels have demonstrated initiatives in supporting cultural preservation, but this involvement has not been formally coordinated. The study recommends enhancing collaboration between the hospitality sector and heritage site managers and developing more structured tourism programs to maximize the potential of Candi Tebing Tegalinggah as a sustainable heritage tourism destination.